Beyond anthropocentrism: ethical pluralism and animal perspectives in Finnish primary school textbooks - Rouhiainen, Henna; Aarnio, Jenna (Taylor & Francis, 2026)
Sustainability transformation requires that Western societies reconsider the values and worldviews they assign to animals. This study examines whether formal education in Finland supports this change by conveying non-anthropocentric and pluralistic ethical perspectives of animals in primary school textbooks. We conducted a theory-based content analysis on history, social studies, environmental studies, religious education, and ethics textbooks, exercises, and teachers’ materials for grades 5–6 in Finland. Our findings reveal that the textbooks contain both anthropocentric and non-anthropocentric ethical perspectives of animals. While anthropocentric and ecocentric worldviews were pronounced, relational perspectives were notably scarce. Additionally, there was a clear discrepancy between different school subjects and different textbook series in the variety and number of perspectives and value discussion. We suggest that textbook publishers aim at increasing ethical reflection, relational perspectives, and a better integration of values and worldviews related to animals across subjects.